Chemical constituents from Crotalaria pallida, Morinda citrifolia and Chlorophyllum molybdites / Siti Rabeah Fadzil - Siti Rabeah , Fadzil (2018)
The present dissertation work focused on the phytochemical studies of three Malaysian plants, Crotalaria pallida, Morinda citrifolia and Chlorophyllum molybdites. C. pallida, from the family of Fabaceae, a herbaceous legume and used traditionally for treatment of several types of illness. This plant is also known to produce the toxic pyrrolizidine alkaloids and flavonoids. M. citrifolia, from the family of Rubiaceae, is a small evergreen shrub tree. It is known to produce anthraquinone compounds, which possess various therapeutic properties including antiviral, antibacterial, antioxidant, anticancer, antitumor, and anti-inflammatory. C. molybdites from the family of Agaricaceae is a poisonous mushroom often involved in poisoning cases throughout the world. This fungi is known to produce the toxic components such as a toxic protein, molybdophyllysin. In the present study, one new cyclopentylidene, crotolidene (CP1), and seven known compounds, i.e. hydroxydihydrobovolide (CP2), octacosane (CP3), trans-phytyl palmitate (CP4), linoleic acid (CP5), methyl oleate (CP6), ethyl palmitate (CP7), and palmitic acid (CP8) were isolated from the hexane extract of C.pallida. A total of five known anthraquinones were isolated from the chloroform extract of M. citrifolia which included damnacanthal (MC1), nordamnacanthal (MC2), rubiadin (MC3), 1,6-dihydroxy-2-methyl-anthraquinone (MC4), 1-hydroxy-3-methoxyanthraquinone (MC5), and 1-methoxy-2-hydroxyanthraquinone (MC6). Ethyl acetate extracts of C. molybdites gave four known compounds which are α-D-glucose (CM1), ethyl-β-D-glucopyranoside (CM2), 2,5-anhydro-D-hexitol (CM3), and linoleic acid (CP5). All the compounds were isolated and characterized using extensive chromatographic and spectroscopic methods.